The Correlation between Students’ Reading Comprehension Skill and Reading Interest in High School - Muhammad Satria Ramanda; Sunarti (EduInovasi: Journal of Basic Educational Studies, 2024)
This study investigates the correlation between reading comprehension skill and reading interest in high school students specifically in English texts. The main objective of this study is to examine the correlation between reading comprehension skill and reading interest in high school students especially in reading English texts. The population of this study consists of second-grade students of a public school in Kutai Kartanegara regency, with cluster sampling will be employed to determine the sample. An English comprehension test and questionnaire of reading interest will serve as the research instrument, and both correlation test and ANOVA will be utilized for data analysis to examine the correlation between reading comprehension skill and reading interest on students. After the data was analyzed with the correlation test, it showed no correlation between students’ reading comprehension and reading interest in high school. According to ANOVA, the result indicated significant differences between the group that has high level of reading interest and those that has low interest. Future research could explore additional variables that may impact reading interests, such as preferences for different genres, motivational factors, and instructional methods aimed at promoting reading for pleasure.